Glutathione and Ascorbic Acid Accumulation in Mango Pulp Under Enhanced UV-B Based on Transcriptome - Hassam Tahir; Muhammad Sajjad; Minjie Qian; Muhammad Zeeshan Ul Haq; Ashar Tahir; Muhammad Aamir Farooq; Ling Wei; Shaopu Shi; Kaibing Zhou; Quansheng Yao (Antioxidants)
Mango (Mangifera indica), a nutritionally rich tropical fruit, is significantly impacted by UV-B radiation, which induces oxidative stress and disrupts physiological processes. This study aimed to investigate mango pulp’s molecular and biochemical responses to UV-B stress (96 kJ/mol) from the unripe to mature stages over three consecutive years, with samples collected at 10-day intervals. UV-B stress affected both non-enzymatic parameters, such as maturity index, reactive oxygen species (ROS) levels, membrane permeability, and key enzymatic components of the ascorbate-glutathione (AsA-GSH) cycle. These enzymes included glutathione reductase (GR), gamma-glutamyl transferase (GGT), glutathione S-transferases (GST), glutathione peroxidase (GPX), glucose-6-phosphate dehydrogenase (G6PDH), galactono-1,4-lactone dehydrogenase (GalLDH), ascorbate peroxidase (APX), ascorbate oxidase (AAO), and monodehydroascorbate reductase (MDHAR). Transcriptomic analysis revealed 18 differentially expressed genes (DEGs) related to the AsA-GSH cycle, including MiGR, MiGGT1, MiGGT2, MiGPX1, MiGPX2, MiGST1, MiGST2, MiGST3, MiG6PDH1, MiG6PDH2, MiGalLDH, MiAPX1, MiAPX2, MiAAO1, MiAAO2, MiAAO3, MiAAO4, and MiMDHAR, validated through qRT-PCR. The findings suggest that UV-B stress activates a complex regulatory network in mango pulp to optimize ROS detoxification and conserve antioxidants, offering insights for enhancing the resilience of tropical fruit trees to environmental stressors.